2008
DOI: 10.1211/jpp.60.8.0004
|View full text |Cite
|
Sign up to set email alerts
|

Cellular effects of long wavelength UV light (UVA) in mammalian cells

Abstract: UVA should receive significant consideration as a human health risk as it is a large proportion of the solar spectrum that reaches the earth's surface and because of its ability to penetrate human skin. It is only relatively recently that this has been recognized and this previously under-researched part of the UV spectrum is becoming increasingly well characterized at doses that are quite low in relation to those experienced by humans. Absorption of UVA in a cell leads to the production of reactive oxygen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 76 publications
3
87
1
8
Order By: Relevance
“…Although studies have shown that the UV-A portion of the spectrum can cause oxidative damage in animal cells (McMillan et al, 2008), studies on marine animals have provided mixed results, with some studies demonstrating negative effects (Adams and Schick, 1996; Karentz et al, 2004) whereas others showed little effect at all (BĂŠland et al, 1999;Kouwenberg et al, 1999). In the present study no significant effects due to exposure to UV-A radiation were observed.…”
Section: Discussioncontrasting
confidence: 56%
“…Although studies have shown that the UV-A portion of the spectrum can cause oxidative damage in animal cells (McMillan et al, 2008), studies on marine animals have provided mixed results, with some studies demonstrating negative effects (Adams and Schick, 1996; Karentz et al, 2004) whereas others showed little effect at all (BĂŠland et al, 1999;Kouwenberg et al, 1999). In the present study no significant effects due to exposure to UV-A radiation were observed.…”
Section: Discussioncontrasting
confidence: 56%
“…Of these, most UVC can be absorbed by the ozone layer. Although the cell-damaging effect of UVA is relatively weak, UVA seems to play an important role in photo-aging because its content in solar UV is higher than UVB and UVC (3)(4)(5). Furthermore, UVB seems to also play the central role in photo-aging (6).…”
mentioning
confidence: 99%
“…The bulk of mitochondrial ROS is generated at the electron transport chain 49,50 . Electrons leak from the electron transport chain directly to oxygen, producing short-lived free radicals such as superoxide anion(O 2 − ) 51 56,57 .…”
Section: Fig 3: Mitochondrial Dysfunction In Agingmentioning
confidence: 99%